# Derivation of Cosine Law

The following are the formulas for cosine law for any triangles with sides a, b, c and angles A, B, C, respectively.

$a^2 = b^2 + c^2 - 2bc\cos A$

$b^2 = a^2 + c^2 - 2ac\cos B$

$c^2 = a^2 + b^2 - 2ab\cos C$

**Derivation:**

Consider the triangle to the right:

Cosine function for triangle ADB

$\cos A = \dfrac{x}{c}$

$x = c\cos A$

Pythagorean theorem for triangle ADB

$x^2 + h^2 = c^2$

$h^2 = c^2 - x^2$

Pythagorean theorem for triangle CDB

$(b - x)^2 + h^2 = a^2$

Substitute h^{2} = c^{2} - x^{2}

$(b - x)^2 + (c^2 - x^2) = a^2$

$(b^2 - 2bx + x^2) + (c^2 - x^2) = a^2$

$b^2 - 2bx + c^2 = a^2$

Substitute x = c cos A

$b^2 - 2b(c \cos A) + c^2 = a^2$

Rearrange:

$a^2 = b^2 + c^2 - 2bc\cos A$

The other two formulas can be derived in the same manner.

Subscribe to MATHalino.com on